Factors Affecting Atlantic Salmon Populations Adversely; Using the River Dee, Scotland, as an Example - Anthony, Hawkins (International Marine Science Journal, 2021)
The stocks of the Atlantic salmon (Salmo salar) in many rivers in North America and Europe have declined in recent years and are experiencing a crisis. Despite their high degree of legal protection, the quality of their aquatic environments within rivers and in the sea, including local coastal waters, appears to be deteriorating. Salmon survival, has declined both within the sea and within rivers. The status of the Atlantic salmon stocks is considered here, together with the adverse effects of different sources, and those steps that may need to be taken to improve the condition of the salmon. This paper is intended to assist management bodies in taking steps to resolve the problems that exist for salmon, both within rivers and in the sea. It makes particular use of information available on the River Dee in Scotland.
Keywords: River; fishes